Interprofessional education in the undergraduate medicine and nursing courses in primary health care practice: The students’ perspective - Santos, Lucas Cardoso Dos [UNESP]; Simonetti, Janete Pessuto [UNESP]; Cyrino, Antonio Pithon [UNESP] (FapUNIFESP (SciELO), 2018)
Currently, in view of the complexity of health problems and the need for a quality and safe care to users, there has been an effort to develop interprofessional education from the beginning of undergraduate health courses. The experience of undergraduate Medicine and Nursing students with interprofessional education is investigated in teaching disciplines in primary healthcare from the perspective of these interlocutors through interviews with a semi-structured script. Data was analyzed according to Bardin’s Thematic Content Analysis. Despite their stereotypes related to the professions, students can learn about colleagues from other courses and with them, and share practices and knowledge. Furthermore, we found out that teachers play an important role as mediators of the teaching-learning process in the development of interprofessional education.
Keywords: Brazil; Higher education; Interprofessional education; Primary healthcare